Transition to adult services for children and young people with palliative care needs: a systematic review. Issue 2 (1st September 2011) - Doug, M; Adi, Y; Williams, J; Paul, M; Kelly, D; Petchey, R; Carter, Y H
Abstract : Objective: To evaluate the evidence on the transition process from child to adult services for young people with palliative care needs. Design: Systematic review. Setting: Child and adult services and interface between healthcare providers. Patients: Young people aged 13–24 years with palliative care conditions in the process of transition. Main outcome measures: Young people and their families' experiences of transition, the process of transition between services and its impact on continuity of care and models of good practice. Results: 92 studies included. Papers on transition services were of variable quality when applied to palliative care contexts. Most focussed on common life-threatening and life-limiting conditions. No standardised transition program identified and most guidelines used to develop transition services were not evidence-based. Most studies on transition programs were predominantly condition-specific (eg, cystic fibrosis (CF), cancer) services. CF services offered high-quality transition with the most robust empirical evaluation. There were differing condition-dependent viewpoints on when transition should occur but agreement on major principles guiding transition planning and probable barriers. There was evidence of poor continuity between child and adult providers with most originating from within child settings. Conclusions: Palliative care was not, in itself, a useful concept for locating transition-related evidence. It is not possible to evaluate the merits of the various transition models for palliative care contexts, or their effects on continuity of care, as there are no long-term outcome data to measure their effectiveness. Use of validated outcome measures would facilitate research and service development.